Enhanced in vivo antimalarial activity of artemether by clotrimazole against drug-sensitive and resistant Plasmodium berghei - Kenechukwu , Franklin C.; Momoh , Mumuni A.; Ugwuoke , Wilfred I.; Nnamani , Daniel O.; Nwobodo , Joy I.; Ogbonna , Jude E.; Nzekwe , Ezichim F.; Nweke , Linda C.; Obila , Mary U.; Odoh , Tochukwu; Odo, Bonaventure A.; Nwagwu , Chinekwu S.; et al. (Journal of Drug Delivery and Therapeutics, 2025)
The emergence of resistance parasites to currently approved artemisinin-based combination therapies (ACTs) highlight the need for regimens incorporating repurposed antimalarials. In this study, we investigated the in vivo performance of artemether/clotrimazole combination against chloroquine-sensitive and multidrug-resistant Plasmodium berghei (Pb) in a preclinical mouse model. The antimalarial activity of artemether, clotrimazole and combination of artemether (8 mg/kg) and clotrimazole (2 mg/kg) was investigated using standard protocols for uncomplicated malaria (UM) and severe malaria (SM) in mice infected with chloroquine-sensitive Pb (CPb) and Pb ANKA (PbA), respectively. Hematological parameters (white blood cells, red blood cells, packed cell volume and haemoglobin) and lethality of infected mice in comparison with controls, tested in parallel, were also monitored. The reduction in parasitemia caused by peroral (p.o.) administration of artemether/clotrimazole combotherapy in CPb-infected mice was significantly greater than artemether monotherapy (**p<0.01), clotrimazole monotherapy (****p<0.0001) and marketed chloroquine (*p<0.05) but less than that obtained with therapeutic dosage of marketed ACT (artemether-lumefantrine) (4mg/24mg/kg x 3 days). Similarly, the reduction in parasitaemia in mice infected with PbA by the combination administered intraperitoneally (i.p.) (12.14%) was significantly higher than monotherapies of artemether (**p<0.01) and clotrimazole (****p<0.0001) but less than commercial i.m. artemether (19.17%). Importantly, the combinations administered both p.o. and i.p. ameliorated Pb-induced alterations in hematological parameters of the malariogenic mice similar with conventional antimalarial regimens (controls). Therefore, artemether/clotrimazole combination would be potential therapeutic options for UM and SM. Our ongoing research would seek to investigate the effect of encapsulating artemether/clotrimazole combinatorial regimen in nanocarriers on the antimalarial activity. Keywords: Plasmodium berghei malaria, Clotrimazole, Drug repurposing, Artemisinin-based combination therapy (ACT), In vivo antimalarial activity, Artemether.